(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Bronchial asthma is a chronic inflammatory disease of the airways characterized by reversible airflow obstruction, bronchial hyperresponsiveness, and recurrent episodes of wheezing, breathlessness, chest tightness, and coughing. It is a major global health problem affecting individuals of all age groups. This article explores the underlying pathophysiology, clinical manifestations, triggering factors, diagnostic approaches, and modern management strategies of bronchial asthma.